Influence of psychosocial factors on student's academic performance in one of Nigerian colleges of education - Kolo, Ali Garba; Wan Jaafar, Wan Munira; Ahmad, Nobaya (Secholian Publication, 2017)
This paper examined the influence of psychosocial factors on student’s academic performance. Self- administered questionnaire was applied as the method of data collection and a sample of 339 students’ from five faculties/schools in Potiskum College were chosen based on stratified and simple random sampling techniques to complete the survey. After analyzing the data collected, Person’s correlation coefficient reflected that, there was a positive and significant correlation between the all four variables: students’ attitudes towards lecturers, academic self-efficacy, students’-lecturers’ interaction and academic performance. Moreover, multiple regression analysis by using stepwise method was conducted to estimate the prediction power of the independent variables on the dependent variable. The finding indicated that only attitude and interaction could significantly predict students’ academic performance by R2=65.6%. Meaning academic self-efficacy failed to predict academic performance in present study. To conclude in this study, attitude and interaction are important factors in influencing students’ academic performance positively in Potiskum College of education, Nigeria.